PENERAPAN CORPORATE SOCIAL RESPONSIBILITY DALAM RITA BARBERSHOP - Maria Helena Chandra; Faustus Efendi Miki (Jurnal Riset Manajemen dan Bisnis, 2024)
ABSTRACT Barbershop is a business that is experiencing rapid growth in Indonesia, including in Nita District, Sikka Regency, East Nusa Tenggara Province. One of the barbershop that capitalizes on this momentum is Rita Barbershop, which not only focuses on haircutting services, but also implements CSR (Corporate Social Responsibility). This study aims to explore more deeply the implementation of CSR at Rita Barbershop which plays a role in providing economic, social, and environmental benefits to the surrounding community, especially for the Ritapiret Higher Seminary Community. This research uses a qualitative case study approach to explore the implementation of CSR at Rita Barbershop and its impact on the Ritapiret Community. A review of relevant literature highlighted the importance of CSR in creating a balance between profit, people and planet. Data was collected through in-depth interviews, field observations, and documentation. The results showed that the implementation of CSR at Rita Barbershop has improved the affordability of hair shaving services, empowered the community, and strengthened social relations. This research is expected to provide insights for other sustainable micro-enterprises. Keywords: Corporate Social Responsibility, Social Entrepreneurship, Rita Barbershop. ABSTRAK Barbershop merupakan bisnis yang sedang mengalami pertumbuhan pesat di Indonesia, termasuk di Kecamatan Nita, Kabupaten Sikka, Provinsi Nusa Tenggara Timur. Salah satu barbershop yang memanfaatkan momentum ini adalah Rita Barbershop, yang tidak hanya fokus pada layanan potong rambut, tetapi juga menerapkan CSR (Corporate Social Responsibility). Penelitian ini bertujuan untuk mengeksplorasi lebih dalam terkait implementasi CSR di Rita Barbershop yang berperan dalam memberikan manfaat ekonomi, sosial, dan lingkungan bagi komunitas sekitar, khususnya untuk Komunitas Seminari Tinggi Ritapiret. Penelitian ini menggunakan pendekatan kualitatif dengan studi kasus untuk mengeksplorasi penerapan CSR di Rita Barbershop dan dampaknya terhadapa Komunitas Ritapiret. Kajian literatur yang relevan menggarisbawahi pentingnya CSR dalam menciptakan keseimbangan antara profit, people, dan planet. Data dikumpulkan melalui wawancara mendalam, observasi lapangan, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan CSR di Rita Barbershop telah meningkatkan keterjangkauan layanan cukur rambut, memberdayakan komunitas, dan memperkuat hubungan sosial. Penelitian ini diharapkan bisa memberikan wawasan bagi usaha mikro lainnya yang berkelanjutan. Kata Kunci: Tanggung Jawab Sosial Perusahaan, Kewirausahaan Sosial, Rita Barbershop.